2011 Triennial Surveillance Review : External Study. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
External Study prepared by Jean Pisani-Ferry, Andre Sapir, and Guntram B. Wolff: This report provides an independent evaluation of recent IMF surveillance in the euro area (EA). It focuses on the euro area as a whole and on four countries severely hit by the recent economic and financial crisis, namely Greece, Ireland, Portugal and Spain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet